ANALISIS PENGELOLAAN OBAT SEBAGAI DASAR PENGENDALIAN SAFETY STOCK OBAT DI PUSKESMAS GANRA KABUPATEN SOPPENG - Khaerani, Khaerani; Haeria, Haeria; Wahyuddin, Munifah; Yulianti, Ika (Jurnal Kesehatan, 2020)
Drug management is an important aspect that include of planning, procurement, acceptance, storage, distribution, to the destruction of drugs. Drug management is a very important thing that needs to be considered, considering that with management that is not in accordance with the proper procedures, overlapping problems will occur. The Pharmacy Installation of the Soppeng District Health Office has carried out drug management but there are still a number of problems namely inadequate human resources, and inadequate facilities. This study aims to determine how the management of drugs in the Department of Health and Community Health Center Soppeng Ganra. This research is a descriptive analysis with a quantitative approach using observational methods. Data collection was carried out using the interview method through questionnaires. The results showed that the management of drugs in the Department of Health and Puskesmas Ganra, Soppeng Regency was not optimal because there were still many shortcomings such as controlling safety stock that had not used good calculations. The results of data percentage based on two different methods obtained 3.48% based on the proposed planning in 2018 and 96.51% using the planning method based on the calculation of safety stock.